Febuxostat efficiently reduces the progression of chronic kidney disease in asymptomatic hyperuricemia: an interventional study - Showkat Azad; Pradip Kumar Dutta; Md Nurul Huda; Mohammad Abdul Kader; Biplob Kumar Barua; Mohammad Shawkat Ali; Maria Mehjabin Akhi; Mishu Rahman; Jannatul Efte Ekra; Md. Sujan Islam; Sadia Afrin; Mohammed Mehadi Hassan Chowdhury; et al. (The Egyptian Journal of Internal Medicine)
Abstract Background Therapeutic approaches for addressing asymptomatic chronic kidney disease (CKD) with renal impairment requires careful consideration, as there is a lack of substantial evidence endorsing specific medications. This study examined the outcomes of administering febuxostat to persons diagnosed with asymptomatic hyperuricemia in CKD (stages 3 and 4). Methods A single-patient blinded; placebo-controlled study was carried out at Chittagong Medical College Hospital in Chattogram 4203 over a 1-year period. Participants were randomly assigned to two groups: one group received a daily dose of 40 mg of febuxostat while the other was given placebo tablets. As necessary, diuretics, antihypertensives, and antidiabetics were administered. Evaluations, which included patient history, physical examinations, outcomes, and pertinent tests, were performed at baseline, the 3rd month, and the 6th month. Results There were 105 similar-baseline patients in each group. The mean serum uric acid (SUA) level in the febuxostat group lowered from 8.55 to 4.92 mg/dL after 6 months, while in the placebo control it elevated from 8.10 to 8.99. In febuxostat group, the mean eGFR elevated from 25.28 to 27.01 ml/min/1.73 m2, while in the placebo control it reduced from 26.81 to 23.32. In the febuxostat group, at the 6-month mark, eGFR differed across groups following a substantial decrease in systolic and diastolic blood pressure (P < 0.05). Conclusions In our clinical setting, febuxostat proved more effective than a placebo in reducing serum uric acid levels and maintaining eGFR in patients with stage 3 and 4 CKD. Hence, febuxostat could be employed to treat hyperuricemia-associated asymptomatic chronic renal disease.